2019
DOI: 10.31703/gssr.2019(iv-ii).28
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants Influencing the Influx of Counterfeit Luxury Goods in Pakistan

Abstract: The demand for counterfeit goods has exponentially grown and counterfeit goods trade has consequently emerged as a global problem. The present study investigates the determinants that encourage consumers to acquire counterfeit luxury goods. This research further analyzes purchase intention as mediator and gender role as a moderator between the contextual factors and consumer behavior. A quantitative approach was applied through a questionnaire to gather data from 380 Pakistani respondents. The measurement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a result, having favorable and negative attitudes about counterfeit products is required to have the intention to purchase or not purchase counterfeit products. Previous research has found that attitude toward counterfeit products modulates the links between materialism, conspicuous consumption, and intention to buy counterfeit products (Saeed et al, 2022;Xi & Cheng, 2017). Although there has been no direct study on the mediation of attitude in the a relationship between sense of shame and intention to purchase counterfeit products, social (peer) pressure will shape a person's intention to purchase or not to purchase counterfeit products by forming a liking or disliking attitude toward counterfeit products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, having favorable and negative attitudes about counterfeit products is required to have the intention to purchase or not purchase counterfeit products. Previous research has found that attitude toward counterfeit products modulates the links between materialism, conspicuous consumption, and intention to buy counterfeit products (Saeed et al, 2022;Xi & Cheng, 2017). Although there has been no direct study on the mediation of attitude in the a relationship between sense of shame and intention to purchase counterfeit products, social (peer) pressure will shape a person's intention to purchase or not to purchase counterfeit products by forming a liking or disliking attitude toward counterfeit products.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the impact of attitude toward counterfeit products in mediating the effects of materialism, conspicuous consumption, and a sense of shame on the intention to purchase counterfeit products is also investigated. There are studies in the literature that look at attitudes regarding counterfeit products as a mediating variable (Xi & Cheng, 2017;Saeed, Nazim & Abbas, 2022;Liaquat et al, 2020). While a good attitude toward counterfeit products boosts the intention to purchase them, a negative attitude inhibits it (Cheng, Fu & Tu, 2011).…”
Section: Mediation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shari and Halym (2006) showed that variables of attitude toward counterfeit products, awareness from value and characteristics of product predict the order for counterfeit video CD. Saeed and Paracha (2019b) showed that economic benefit, materialism and hedonic motive were related to consumer behavior about counterfeit luxury goods.…”
Section: Theoretical Literature and Research Backgroundmentioning
confidence: 99%
“…Furthermore, due to ineffective law enforcement, consumers in developing countries, that is, Pakistan, are increasingly turning to counterfeit products ( Niaz, 2020 ). Pakistan is among the top 10 nations globally from where the counterfeit products originate, and counterfeit goods are readily accessible and marketed openly throughout the country ( Saeed and Sadiq Paracha, 2019 ). The presence and spread of counterfeiting are directly linked to customer demand, which is the primary driving factor behind every market.…”
Section: Introductionmentioning
confidence: 99%